SAVI-based animated video for seismic material - Mohammad Yusril Abidin; Alfi Sahrina; Fatiya Rosyida; Djoko Soelistijo (Jurnal Pendidikan Geografi: Kajian, Teori, dan Praktek dalam Bidang Pendidikan dan Ilmu Geografi, 2024)
Learning media supports effective and efficient learning. Meanwhile, seismic learning is deemed as a challenging geography course, thereby, requiring animated video as a medium to visualize abstract concepts into concrete ones. Thus, this study formulates animated learning videos using the SAVI approach for seismic material. It also assesses the effect of animated video media on student learning outcomes. The animation video was constructed using the ADDIE research model and tried out in a pre-experimental pretest-posttest type one group design. The trial was conducted involving 27 tenth grade students from Sunan Ampel Islamic Senior High School. The results of the validity test from the material expert indicate an 88 percent agreement rate, while the media expert shows an 87.3 percent agreement rate. The teacher's response questionnaire received a score of 97 percent, while the student responses received a score of 88%. After attending learning with animated video, the average student score increased from 51.31 to 83.77 in the pretest and posttest results. The data obtained from the normality test showed a normal distribution, while the t-test suggested significant results with sig. (2-tailed) 0.000 lees than 0.05. These results imply a significant difference in students' skills before and after the use of animated video media. In summary, the developed media is suitable for seismic learning, offering a positive impact on student learning outcomes.